Fundamentals of Microwave and RF Design - Steer, Michael (Open textbook library., 2019)
Fundamentals of Microwave and RF Design enables mastery of the essential concepts required to cross the barriers to a successful career in microwave and RF design. Extensive treatment of scattering parameters, that naturally describe power flow, and of Smith-chart-based design procedures prepare the student for success. The emphasis is on design at the module level and on covering the whole range of microwave functions available. The orientation is towards using microstrip transmission line technologies and on gaining essential mathematical, graphical and design skills for module design proficiency. This book is derived from a multi volume comprehensive book series, Microwave and RF Design, Volumes 1-5, with the emphasis in this book being on presenting the fundamental materials required to gain entry to RF and microwave design. This book closely parallels the companion series that can be consulted for in-depth analysis with referencing of the book series being familiar and welcoming.